The Response of Critical Microbial Taxa to Litter Micro-Nutrients and Macro-Chemistry Determined the Agricultural Soil Priming Intensity After Afforestation - Yang, Hongling; Li, Yulin; Wang, Shaokun; Zhan, Jin; Ning, Zhiying; Han, Dan (Frontiers in Microbiology, 2021)
Afforestation with trees and shrubs around cropland can effectively decrease soil degradation and avoid sand storms, but subsequent modification of litter quality accelerates the degradation of native organic matter via the soil priming effect (PE). Although carbon accumulation in agricultural soils after afforestation was widely studied, little is known about the extent to which soil organic carbon (SOC) mineralization is induced by complex residue input in agro-forest-grass composite ecosystems. Here, we mixed corn field soil and litter of afforestation tree and shrub species together in a micro-environment to quantify the effects of litter-mixture input on farmland soil priming associated with afforestation. Additionally, we studied the responses of bacterial and fungal species to litter chemistry, with the aim to identify the litter and microbial driver of soil priming. The results showed that soil priming was accelerated by different litter addition which varied from 24% to 74% of SOC mineralization, suggesting that priming intensity was relatively flexible and highly affected by litter quality. We also find that the macro-chemistry (including litter carbon, nitrogen, lignin and cellulose) directly affects priming intensity, while micro-chemistry (including litter soluble sugar, water-soluble phenol, methanol-soluble phenol, and condensed tannin) indirectly influences priming via alteration to dominant bacterial taxa. The stepwise regression analysis suggested that litter nitrogen and cellulose were the critical litter drivers to soil priming(R2=0.279), and the combination of bacterial phylum Proteobacteria, Firmicutes, Bacteroidetes, Acidobacteria, and fungal taxa Eurotiomycetes was a great model to explain the priming intensity(R2=0.407).